A method for preparing hydrogen-sensitive material by attaching palladium nanoparticles to a composite material of carbon nanofiber and ZnO
The carbon nanofiber and ZnO composite material was prepared by electrospinning technology, and the PdCl2 solution was applied to its surface by impregnation method, so that the palladium nanoparticles were evenly distributed and effectively anchored, solving the problem of uneven distribution of palladium particles on carbon nanofibers and improving the performance of the hydrogen sensor.
Patent Information
- Application Number
- CN202411848364.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-01
AI Technical Summary
The palladium particles cannot be uniformly distributed and effectively anchored on carbon nanofibers, resulting in limited sensitivity and stability of hydrogen sensors, and the inability to achieve long-term stable detection and accurate signal output in complex gas environments.
The carbon nanofiber and ZnO composite material was prepared by electrospinning technology, and the PdCl2 solution was applied to its surface by impregnation method, so that the palladium nanoparticles were evenly distributed and effectively anchored.
The uniform distribution and effective anchoring of palladium nanoparticles are achieved, the response speed, sensitivity, selectivity and stability of the hydrogen sensor are improved, and the response speed, sensitivity, selectivity and stability can be quickly responded at low hydrogen concentrations.
Smart Images

Figure CN119733827A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field related to electrostatic spinning, and in particular to a method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a composite material of carbon nanofibers and ZnO. Background Art
[0002] Electrospinning technology is a processing technology that uses electric field force to spin polymer solutions or melts. It is widely used to prepare nano-sized fibers. Electrospinning technology can prepare carbon nanofibers with uniform diameter distribution and controllable pore size. These fibers have excellent physical and chemical properties, making them popular in many fields.
[0003] Palladium metal is widely used as a hydrogen sensor material due to its high sensitivity and selectivity to hydrogen. However, palladium particles cannot be evenly distributed and effectively anchored on carbon nanofibers, resulting in limited sensitivity and stability of the sensor. It is unable to achieve long-term stable detection and accurate signal output in complex gas environments, and its scope of use is relatively limited. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a carbon nanofiber and ZnO composite material, so as to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a carbon nanofiber and ZnO composite material, comprising the following steps:
[0006] S1: adding polyacrylonitrile to N,N-dimethylformamide, and preparing a first solution by magnetic stirring, and adding anhydrous zinc acetate to the first solution and magnetically stirring again to obtain an electrospinning precursor solution;
[0007] S2: loading the precursor solution into a syringe, and preparing a carbon nanofiber and ZnO composite material by electrospinning technology;
[0008] S3: heat-treating the material obtained in S2 to obtain a treated carbon nanofiber and ZnO composite material through pre-oxidation, oxidation and carbonization;
[0009] S4: preparing a PdCl2 precursor solution;
[0010] S5: adding deionized water and anhydrous ethanol to the PdCl2 precursor solution obtained in S4, and then preparing a NaOH solution and adding it to the above solution, adjusting the pH value of the mixed solution to 5;
[0011] S6: immersing the carbon nanofiber and ZnO composite material prepared in S3 into the mixed solution with a pH value of 5 in S5 to deposit Pd;
[0012] S7: After soaking, the sample is washed with water and ethanol, and then dried in an oven to obtain a carbon nanofiber and ZnO composite material with palladium nanoparticles attached to the surface.
[0013] Preferably, in step S1, polyacrylonitrile is added to N,N-dimethylformamide, and the first solution is prepared by magnetic stirring, and the specific method includes:
[0014] 1 g of polyacrylonitrile with a molecular weight of 150,000 was added to 10 ml of N,N-dimethylformamide, and the mixture was heated at 90° C. in a water bath and magnetically stirred for 2 h to prepare a first solution.
[0015] Preferably, in step S1, anhydrous zinc acetate is added to the first solution and magnetically stirred again to obtain an electrospinning precursor solution, and the specific method includes:
[0016] 0.7 g of anhydrous zinc acetate was added to the first solution, and the solution was heated in a water bath at 90° C. with magnetic stirring for 2 h to obtain a precursor solution.
[0017] Preferably, in step S2, the precursor solution is loaded into a syringe, and the specific method of preparing the carbon nanofiber and ZnO composite material by electrospinning technology includes:
[0018] The precursor solution was loaded into a 20 ml syringe with a needle of 23G. The syringe spinning speed was controlled to be 15 μl / min. The distance between the syringe needle tip and the collector was 18 cm. A voltage of 25 KV was applied. The relative humidity of the electrospinning environment was controlled within the range of 45% ± 2%, and the temperature was 28°C. The carbon nanofiber and ZnO composite material was collected on the collector.
[0019] Preferably, the heat treatment in step S3 comprises the following steps:
[0020] S31: pre-oxidation stage, heating the carbon nanofiber and ZnO composite material from room temperature to 220°C at a heating rate of 1°C / min and maintaining the pre-oxidation treatment for 1h;
[0021] S32: oxidation stage, heating the carbon nanofiber and ZnO composite material from 220°C to 410°C at a heating rate of 5°C / min and maintaining the temperature for 1 h for oxidation treatment;
[0022] S33: In the carbonization stage, argon gas is introduced, and the temperature of the carbon nanofiber and ZnO composite material is raised from 410° C. to 600° C. at a heating rate of 2° C. / min and maintained for 1 hour to obtain a treated carbon nanofiber and ZnO composite material.
[0023] Preferably, the heat treatment of the carbon nanofiber and ZnO composite material in step S3 is performed in a tubular furnace.
[0024] Preferably, in step S4, PdCl is prepared 2 Specific methods for the precursor solution include:
[0025] 0.106 g PdCl 2 The powder was dissolved in 10 drops of 6 mol / L hydrochloric acid solution, left to stand for 10 min to dissolve, and then 5 ml of deionized water was added to turn it into a brown transparent chloropalladic acid solution.
[0026] Preferably, in step S5, deionized water and anhydrous ethanol are added to the PdCl obtained in step S4. 2 The precursor solution is then mixed with a NaOH solution and added to the above solution to adjust the pH value of the mixed solution to 5. The specific method includes:
[0027] Add 60 ml of deionized water and 30 ml of anhydrous ethanol to the PdCl obtained in step S4. 2 The pH value of the precursor solution is 3 at this time. Then add NaOH solid to 20 ml of water to prepare NaOH solution. Drop the prepared NaOH solution into the mixed solution and continuously test the pH value until the pH value of the solution is adjusted to 5.
[0028] Preferably, in step S6, the carbon nanofiber and ZnO composite material is immersed in the mixed solution with a pH of 5 in step 5 until the solution becomes clear and transparent, indicating that Pd 2+ is fully extracted.
[0029] Preferably, the sample after immersion in step S7 is washed alternately with deionized water and ethanol three times, and then placed in an oven at 70° C. for drying to obtain a carbon nanofiber and ZnO composite material with palladium nanoparticles attached to the surface.
[0030] Technical effects and advantages of the present invention:
[0031] The present invention uses electrospinning technology to prepare carbon nanofiber and ZnO composite materials, and PdCl 2The solution is coated on the surface of the carbon nanofiber and ZnO composite material, and the palladium nanoparticles are evenly distributed on the carbon nanofiber to form a carbon nanofiber and ZnO composite material with palladium nanoparticles attached to the surface. The palladium particles can be effectively anchored on the surface of the carbon nanofiber and ZnO composite material. The carbon nanofiber and ZnO composite material with palladium nanoparticles attached to the surface has a high resistance change after absorbing hydrogen, and can respond quickly under low hydrogen concentration, showing excellent hydrogen sensing performance. This fibrous hybrid material is developed not only to improve the response speed and sensitivity of the hydrogen sensor, but also enhance its selectivity and stability in complex gas environments, making it easy to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The present invention is a flow chart of the preparation method of the hydrogen-sensitive material prepared by attaching palladium nanoparticles to the carbon nanofiber and ZnO composite material.
[0033] Figure 2 This is a heat treatment flow chart of the spun carbon nanofiber and ZnO composite material of the present invention.
[0034] Figure 3 This is the response diagram of palladium nanoparticles attached to the surface of the carbon nanofiber and Zn0 composite material of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention provides Figure 1-3 The method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a carbon nanofiber and ZnO composite material comprises the following steps:
[0037] S1: adding polyacrylonitrile to N,N-dimethylformamide, and preparing a first solution by magnetic stirring, and adding anhydrous zinc acetate to the first solution and magnetically stirring again to obtain an electrospinning precursor solution;
[0038] S2: The precursor solution is loaded into a syringe and the carbon nanofiber and ZnO composite material is prepared by electrospinning technology;
[0039] S3: heat-treating the material obtained in S2 to obtain a treated carbon nanofiber and ZnO composite material through pre-oxidation, oxidation and carbonization;
[0040] S4: Preparation of PdCl 2 Precursor solution;
[0041] S5: Add deionized water and anhydrous ethanol to the PdCl obtained in S4 2 The precursor solution is then mixed with NaOH solution and added to the above solution to adjust the pH value of the mixed solution to 5;
[0042] S6: immersing the carbon nanofiber and ZnO composite material prepared in S3 into the mixed solution with a pH value of 5 in S5 to deposit Pd;
[0043] S7: After soaking, the sample is washed with water and ethanol, and then dried in an oven to obtain a carbon nanofiber and ZnO composite material with palladium nanoparticles attached to the surface.
[0044] Through the above steps, the carbon nanofiber and ZnO composite material can be prepared by electrospinning technology, and PdCl 2 The solution is coated on the surface of the carbon nanofiber and ZnO composite material, and the palladium nanoparticles are evenly distributed on the carbon nanofiber to form a carbon nanofiber and ZnO composite material with palladium nanoparticles attached to the surface. The palladium particles can be effectively anchored on the surface of the carbon nanofiber and ZnO composite material. The carbon nanofiber and ZnO composite material with palladium nanoparticles attached to the surface has a high resistance change after absorbing hydrogen, and can respond quickly under low hydrogen concentration, showing excellent hydrogen sensing performance. This fibrous hybrid material is developed not only to improve the response speed and sensitivity of the hydrogen sensor, but also enhance its selectivity and stability in complex gas environments, making it easy to use.
[0045] Specifically, in step S1, polyacrylonitrile is added to N,N-dimethylformamide, and a first solution is prepared by magnetic stirring. The specific method includes:
[0046] 1 g of polyacrylonitrile with a molecular weight of 150,000 was added to 10 ml of N, N-dimethylformamide, and the first solution was prepared by heating at 90°C in a water bath and magnetically stirring for 2 hours. Heating at 90°C in a water bath can provide a suitable temperature environment, which can promote the better dissolution and dispersion of polyacrylonitrile in N, N-dimethylformamide and help form a uniform solution system. Magnetic stirring for 2 hours can enhance the mixing effect, avoid local uneven concentration or precipitation of polyacrylonitrile in the solvent, make the polyacrylonitrile molecules fully contact with the solvent, improve the dissolution efficiency, and thus obtain a stable and uniform first solution, which provides a good foundation for subsequent processing and application. The obtained uniform solution is convenient for subsequent electrospinning and other processing techniques.
[0047] Furthermore, in step S1, anhydrous zinc acetate is added to the first solution and magnetically stirred again to obtain an electrospinning precursor solution, and the specific method includes:
[0048] 0.7 g of anhydrous zinc acetate was added to the first solution, and a precursor solution was prepared by heating in a water bath at 90°C and magnetically stirring for 2 hours. Heating in a water bath at 90°C and magnetically stirring for 2 hours can promote the uniform dispersion of anhydrous zinc acetate in the first solution. Magnetic stirring ensures the full mixing of the solution system, so that the zinc acetate molecules can be evenly distributed throughout the solution, avoiding the situation where the local concentration is too high or too low. Heating in a water bath provides a stable temperature environment, which is conducive to the dissolution and reaction of zinc acetate, and helps to form a uniform precursor solution. The uniform precursor solution is conducive to the subsequent preparation of composite fibers with specific morphology and structure through electrospinning and other technologies. The introduction of zinc acetate may give the final prepared material some special properties, such as enhanced conductivity, catalytic activity, etc. By controlling the amount of zinc acetate added and the reaction conditions, the performance of the material can be adjusted and optimized to meet the needs of different applications.
[0049] Specifically, in step S2, the precursor solution is loaded into a syringe, and the specific method of preparing the carbon nanofiber and ZnO composite material by using electrospinning technology includes:
[0050] The precursor solution is loaded into a 20ml syringe with a needle of 23G. The syringe spinning speed is controlled to be 15μl / min. Controlling the syringe spinning speed to be 15μl / min can ensure that the solution is ejected at a relatively stable rate, which is conducive to the formation of uniform fibers with relatively consistent diameters. The slower spinning speed helps to better control the fiber formation process and avoid problems such as uneven fiber thickness. The distance between the syringe needle tip and the collector is 18cm. This distance is conducive to the relatively smooth migration and stretching of the fiber to the collector under the action of the electric field to form a longer fiber structure. At the same time, it can also better control the deposition density of the fiber, etc., and apply a voltage of 25KV. Applying a voltage of 25KV can generate a strong electric field force, which prompts the precursor solution to be electrostatically spun under the action of the electric field, so that the polymers and additives in the solution form a fibrous structure driven by the electric field force. A higher voltage helps to overcome the surface tension of the solution, so that the fiber can be ejected and stretched smoothly. The relative humidity of the electrospinning environment is controlled within the range of 45% ± 2%, and the temperature is 28 ° C. The carbon nanofiber and ZnO composite material is collected on the collector. Appropriate humidity can affect the surface properties and volatilization rate of the solution, etc., which is helpful for the formation and stable deposition of the fiber, and avoids problems such as too fast volatilization of the solution due to excessive humidity or static electricity accumulation due to too low humidity that affect the stability of the spinning process. The temperature of 28 ° C provides a suitable ambient temperature, which is conducive to the fluidity of the solution and the spinning process. The carbon nanofiber and ZnO composite material prepared in this way has a relatively uniform microstructure, including the diameter of the fiber and the distribution of ZnO on the carbon nanofiber. It is relatively uniform, which is conducive to the material showing stable performance in subsequent applications.
[0051] Furthermore, the heat treatment in step S3 includes the following steps:
[0052] S31: Pre-oxidation stage, the carbon nanofiber and ZnO composite material is heated from room temperature to 220°C at a heating rate of 1°C / min and maintained for 1h for pre-oxidation treatment, which can gradually oxidize the organic components in the carbon nanofiber and ZnO composite material to form a stable oxidation structure, enhance the thermal stability of the material during subsequent high-temperature treatment, avoid violent reaction and decomposition of organic matter caused by rapid heating, reduce the generation of defects, and lay the foundation for subsequent treatment;
[0053] S32: oxidation stage, heating the carbon nanofiber and ZnO composite material from 220°C to 410°C at a heating rate of 5°C / min and maintaining the temperature for 1h for further deep oxidation to remove the residual unstable structure and impurities, improve the surface chemical properties of the material, make the bond between ZnO and carbon nanofiber stronger, and help form a more uniform microstructure, thereby improving the overall performance of the material;
[0054] S33: In the carbonization stage, argon is introduced, and the temperature of the carbon nanofiber and ZnO composite material is increased from 410°C to 600°C at a heating rate of 2°C / min and maintained for 1 hour to obtain a treated carbon nanofiber and ZnO composite material. Argon is introduced as a protective gas to prevent the material from reacting with oxygen in the air at high temperature and being oxidized. The temperature is increased from 410°C to 600°C at a heating rate of 2°C / min and maintained for 1 hour to further graphitize the carbon nanofiber, thereby improving its conductivity and thermal stability, and at the same time allowing ZnO to be better dispersed in the carbon nanofiber, forming a composite structure with unique properties, thereby enhancing the performance of the material in various applications.
[0055] Furthermore, in step S3, the heat treatment of the carbon nanofiber and ZnO composite material is carried out in a tubular furnace. The entire heat treatment process is carried out in a tubular furnace, which can provide a uniform temperature environment, facilitate precise control of the heating rate and temperature, ensure the stability and repeatability of the heat treatment process, and is conducive to obtaining high-quality, stable-performance treated carbon nanofiber and ZnO composite materials.
[0056] Specifically, in step S4, PdCl is prepared 2 Specific methods for the precursor solution include:
[0057] 0.106 g PdCl 2 The powder was dissolved in 10 drops of 6 mol / L hydrochloric acid solution, left to stand for 10 minutes to dissolve, and then 5 ml of deionized water was added to turn it into a brown transparent chloropalladic acid solution. The 6 mol / L hydrochloric acid solution can provide a suitable acidic environment to help PdCl 2 To dissolve the powder, hydrochloric acid can react with PdCl2 The reaction occurs, promoting its dispersion in the solution. By standing for 10 minutes, the dissolution process can be more complete, ensuring that PdCl 2 Complete dissolution to obtain a uniform precursor solution composition provides a good basis for the subsequent preparation of Pd-related substances. At the same time, the formed brown transparent chloropalladic acid solution has specific optical properties and chemical composition. This specific solution state is conducive to uniform mixing and interaction with other substances in the subsequent reaction or treatment process, which is convenient for controlling the progress of the reaction and the uniformity of the product.
[0058] Specifically, in step S5, deionized water and anhydrous ethanol are added to the PdCl obtained in step S4. 2 The precursor solution is then mixed with a NaOH solution and added to the above solution to adjust the pH value of the mixed solution to 5. The specific method includes:
[0059] Add 60 ml of deionized water and 30 ml of anhydrous ethanol to the PdCl obtained in step S4. 2 In the precursor solution, the pH value is 3 at this time. Then add NaOH solid to 20ml water to prepare NaOH solution. Drop the prepared NaOH solution into the mixed solution and continuously test the pH value until the pH of the solution is adjusted to 5. First add deionized water and anhydrous ethanol. Deionized water can provide a pure solvent environment, which helps the dissolved substances to be evenly dispersed therein; the addition of anhydrous ethanol can change the polarity and other properties of the solution, and synergize with deionized water to make the subsequent added substances better dissolved and reacted. The addition of both can improve the properties of the entire solution system and provide a more suitable environment for subsequent reactions. First, make the pH value of the initial mixed solution 3, and then adjust the pH to 5 by dropping NaOH solution. This step-by-step operation can more finely control the pH change process of the solution. Slowly dropping and continuously testing the pH value can avoid the rapid change of pH value leading to instability of the reaction system or unnecessary side reactions, and ensure that the pH of the solution can be smoothly adjusted to the target value of 5, which is conducive to the subsequent reaction with PdCl 2 The reaction of precursors and other substances can be carried out in a suitable acid-base environment, which is conducive to generating the desired product or achieving a specific reaction effect.
[0060] Specifically, in step S6, the carbon nanofiber and ZnO composite material is immersed in the mixed solution with a pH of 5 in step 5 until the solution becomes clear and transparent, indicating that Pd 2+ The Pd 2+ This intuitive judgment method can accurately reflect the completion of the extraction process and ensure that all Pd 2+The Pd was transferred from the solution to the carbon nanofiber and ZnO composite material, avoiding the problems of unstable material performance or incomplete subsequent reaction caused by incomplete extraction. The clear reaction phenomenon, that is, the solution changes from turbid to clear, makes the whole extraction process easy to monitor and control. The operator can adjust the operation steps or judge the progress of the reaction in time according to the changes in the solution, which improves the repeatability and reliability of the experiment and completely extracts Pd. 2+ After extraction, the Pd element will be loaded on the carbon nanofiber and ZnO composite material, which helps to improve the performance of the composite material. For example, the presence of Pd may give the composite material good catalytic activity and conductivity, so that it has a wider application prospect in the fields of catalysis and sensors. Through this clear extraction and judgment method, the loading amount and uniformity of the Pd element can be guaranteed, thereby better playing its role in improving the performance of the composite material.
[0061] Specifically, the sample after immersion in step S7 is washed three times with deionized water and ethanol alternately, and then dried in a 70°C oven to obtain a carbon nanofiber and ZnO composite material with palladium nanoparticles attached to the surface. The sample is washed three times with deionized water and ethanol alternately, which can effectively remove impurities, unreacted substances, and other ions that may be adsorbed during the immersion process. Deionized water can remove water-soluble impurities, and ethanol can dissolve some organic impurities and volatilize them. Alternate washing can more thoroughly remove surface pollutants and improve the purity of the sample. The washed sample is placed in a 70°C oven for drying. The appropriate temperature helps to quickly remove the residual moisture on the sample surface to avoid the adverse effects of moisture on the sample during subsequent processing or storage, such as causing the sample to deteriorate and affecting its performance. At the same time, this temperature will not cause thermal damage to components such as palladium nanoparticles, carbon nanofibers and ZnO in the sample, and can ensure the stability of the sample's structure and performance. The carbon nanofiber and ZnO composite materials with palladium nanoparticles attached to the surface obtained after such treatment have fewer surface impurities and low residual moisture, which is conducive to more stable attachment of palladium nanoparticles to the surface of carbon nanofiber and ZnO composite materials, thereby better exerting the characteristics of palladium nanoparticles. This pure and dry state helps to improve the performance and stability of the composite materials in various applications.
[0062] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a carbon nanofiber and ZnO composite material, characterized in that: The following steps are involved: S1: adding polyacrylonitrile to N,N-dimethylformamide, and preparing a first solution by magnetic stirring, and adding anhydrous zinc acetate to the first solution and magnetically stirring again to obtain an electrospinning precursor solution; S2: loading the precursor solution into a syringe, and preparing a carbon nanofiber and ZnO composite material by electrospinning technology; S3: heat-treating the material obtained in S2 to obtain a treated carbon nanofiber and ZnO composite material through pre-oxidation, oxidation and carbonization; S4: preparing a PdCl2 precursor solution; S5: adding deionized water and anhydrous ethanol to the PdCl2 precursor solution obtained in S4, and then preparing a NaOH solution and adding it to the above solution, adjusting the pH value of the mixed solution to 5; S6: immersing the carbon nanofiber and ZnO composite material prepared in S3 into the mixed solution with a pH value of 5 in S5 to deposit Pd; S7: After soaking, the sample is washed with water and ethanol, and then dried in an oven to obtain a carbon nanofiber and ZnO composite material with palladium nanoparticles attached to the surface.
2. The method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a carbon nanofiber and ZnO composite material according to claim 1, characterized in that: In step S1, polyacrylonitrile is added to N,N-dimethylformamide, and a first solution is prepared by magnetic stirring. The specific method includes: 1 g of polyacrylonitrile with a molecular weight of 150,000 was added to 10 ml of N,N-dimethylformamide, and the mixture was heated at 90° C. in a water bath and magnetically stirred for 2 h to prepare a first solution.
3. The method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a carbon nanofiber and ZnO composite material according to claim 1, characterized in that: In step S1, anhydrous zinc acetate is added to the first solution and magnetically stirred again to obtain an electrospinning precursor solution, and the specific method includes: 0.7 g of anhydrous zinc acetate was added to the first solution, and the solution was heated in a water bath at 90° C. with magnetic stirring for 2 h to obtain a precursor solution.
4. The method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a composite material of carbon nanofibers and ZnO according to claim 1, characterized in that: The specific method of preparing the carbon nanofiber and ZnO composite material by electrospinning technology in step S2 is as follows: The precursor solution was loaded into a 20 ml syringe with a needle of 23G. The syringe spinning speed was controlled to be 15 μl / min. The distance between the syringe needle tip and the collector was 18 cm. A voltage of 25 KV was applied. The relative humidity of the electrospinning environment was controlled within the range of 45% ± 2%, and the temperature was 28°C. The carbon nanofiber and ZnO composite material was collected on the collector.
5. The method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a composite material of carbon nanofibers and ZnO according to claim 1, characterized in that: The heat treatment in step S3 includes the following steps: S31: pre-oxidation stage, heating the carbon nanofiber and ZnO composite material from room temperature to 220°C at a heating rate of 1°C / min and maintaining the pre-oxidation treatment for 1h; S32: oxidation stage, heating the carbon nanofiber and ZnO composite material from 220°C to 410°C at a heating rate of 5°C / min and maintaining the temperature for 1 h for oxidation treatment; S33: In the carbonization stage, argon gas is introduced, and the temperature of the carbon nanofiber and ZnO composite material is raised from 410° C. to 600° C. at a heating rate of 2° C. / min and maintained for 1 hour to obtain a treated carbon nanofiber and ZnO composite material.
6. The method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a composite material of carbon nanofibers and ZnO according to claim 1, characterized in that: In step S3, the heat treatment of the carbon nanofiber and ZnO composite material is carried out in a tubular furnace.
7. The method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a composite material of carbon nanofibers and ZnO according to claim 1, characterized in that: The specific method for preparing the PdCl2 precursor solution in step S4 includes: Dissolve 0.106g PdCl2 powder in 10 drops of 6mol / L hydrochloric acid solution, let it stand for 10 minutes to dissolve, and then add 5ml deionized water to turn it into a brown transparent chloropalladic acid solution.
8. The method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a composite material of carbon nanofibers and ZnO according to claim 1, characterized in that: In step S5, deionized water and anhydrous ethanol are added to the PdCl2 precursor solution obtained in step S4, and then a NaOH solution is prepared and added to the above solution to adjust the pH value of the mixed solution to 5. The specific method includes: Add 60 ml of deionized water and 30 ml of anhydrous ethanol to the PdCl2 precursor solution obtained in step S4. At this time, the pH value is 3. Then add NaOH solid to 20 ml of water to prepare NaOH solution. Add the prepared NaOH solution dropwise into the mixed solution and continuously test the pH value until the pH of the solution is adjusted to 5.
9. The method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a composite material of carbon nanofibers and ZnO according to claim 1, characterized in that: In step S6, the carbon nanofiber and ZnO composite material is immersed in the mixed solution with a pH of 5 in step 5 until the solution becomes clear and transparent, indicating that Pd 2+ is fully extracted.
10. The method for preparing a hydrogen-sensitive material by attaching palladium nanoparticles to a composite material of carbon nanofibers and ZnO according to claim 1, characterized in that: After the sample is immersed in step S7, it is washed alternately with deionized water and ethanol three times, and then placed in an oven at 70° C. for drying to obtain a carbon nanofiber and ZnO composite material with palladium nanoparticles attached to the surface.